Adsorption, modeling, thermodynamic, and kinetic studies of Acteray Golden removal from polluted water using Sindh clay and quartz as low-cost adsorbents - Fatima, Aqsa; Hanif, Muhammad Asif; Rashid, Umer; Jilani, Muhammad Idrees; Alharthi, Fahad A.; Han, Jeehoon (Multidisciplinary Digital Publishing Institute, 2023)
Due to growing environmental awareness and demands, many efforts were implemented for the transformation of waste materials into highly efficient adsorption capacity materials. In this work, efforts were made to convert the Sindh clay and quartz into an efficient composite for dye removal from polluted water. The synthesized composites were characterized using FT-IR, BET, SEM, and XRD. The synthesized composite showed a crystalline structure with specific characteristics, including a specific surface area of 7.20 m2/g and a pore diameter of 3.27 nm. The formation of iron cyanide hydrate (2030 cm−1) and iron oxides (418 cm−1) were depicted through Fourier transform infrared spectroscopy analysis. The micrographs obtained show that the unmodified quartz sample has a flattened and elongated shape compared to the modified quartz sample, which has aggregated and coarse morphology. The effects of several factors, such as temperature, contact time, and initial dye concentration, were studied. Kinetic models were also applied to determine the probable route of the adsorption process. For adsorption equilibrium analysis, the Dubinin–Radushkevich, Langmuir, Freundlich, Temkin, and Harkin–Juraisotherm models were employed. The Freundlich isotherm model and pseudo-first-order model best described the adsorption of dyes onto the clay composites. R2 values were close to 1 or more than 0.9, showing which equation fits the experimental data. The produced composite demonstrated good reusability, maintaining over 90% of the adsorption capacity after five reaction cycles without the need for reactivation.